Dear Mr. Henshaw - Cleary, Beverly; Zelinsky, Paul O. (New York : HarperTrophy, 2000)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents' divorce, being the new boy in school, and generally finding his own place in the world.
Ages 8-12.
Newbery Medal
ALA notable book
Keywords: Parent and child -- Juvenile fiction; Children of divorced parents -- Juvenile fiction; Children of divorced parents; Parent and child; Epistoloary fiction; Fiction; Juvenile works